Zero-Hopf bifurcation in the FitzHugh-Nagumo system - Euzébio, Rodrigo D. [UNESP]; Llibre, Jaume; Vidal, Claudio (Wiley, 2015)
We characterize the values of the parameters for which a zero-Hopf equilibrium point takes place at the singular points, namely, O (the origin), P+, and P- in the FitzHugh-Nagumo system. We find two two-parameter families of the FitzHugh-Nagumo system for which the equilibrium point at the origin is a zero-Hopf equilibrium. For these two families, we prove the existence of a periodic orbit bifurcating from the zero-Hopf equilibrium point O. We prove that there exist three two-parameter families of the FitzHugh-Nagumo system for which the equilibrium point at P+ and at P- is a zero-Hopf equilibrium point. For one of these families, we prove the existence of one, two, or three periodic orbits starting at P+ and P-.
Keywords: averaging theory; FitzHugh-Nagumo system; periodic orbit; zero-Hopf bifurcation